2004
DOI: 10.1593/neo.04298
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibody 16D10 to the C-Terminal Domain of the Feto-Acinar Pancreatic Protein Binds to Membrane of Human Pancreatic Tumoral SOJ-6 Cells and Inhibits the Growth of Tumor Xenografts

Abstract: Feto-acinar pancreatic protein (FAPP) characterized by mAbJ28 reactivity is a specific component associated with ontogenesis and behaves as an oncodevelopment-associated antigen. We attempted to determine whether pancreatic tumoral SOJ-6 cells are expressed at their surface FAPP antigens and to examine if specific antibodies directed against these FAPP epitopes could decrease the growth of pancreatic tumors in a mice model. For this purpose, we used specific antibodies against either the whole FAPP, the O-glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 57 publications
1
23
0
Order By: Relevance
“…I.p. injections of mAb16D10 in mice xenotransplanted with SOJ-6 cells decreased the growth rate of the established tumor (23). Opposite to mAb16D10, the mAbJ28 recognizes pancreatic tumor, but it has no effect on tumor growth.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…I.p. injections of mAb16D10 in mice xenotransplanted with SOJ-6 cells decreased the growth rate of the established tumor (23). Opposite to mAb16D10, the mAbJ28 recognizes pancreatic tumor, but it has no effect on tumor growth.…”
Section: Discussionmentioning
confidence: 94%
“…These studies included immunocytologic localization of FAPP within human pancreatic tumoral tissue compared with normal tissue (19) and the targeting of nitrosamine-induced pancreatic tumor in hamster (which expressed the J28 epitope) with the radiolabeled mAbJ28 (47). A recent study showed that the mucin-like COOH-terminal domain of FAPP is actually presented at the surface of human pancreatic tumoral SOJ-6 cells (23). This glycopeptide is recognized by mAbJ28 and mAb16D10.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…FAPP is a glycoform of bile saltdependent lipase (BSDL) (31,32), a lipolytic enzyme present in normal human pancreatic juices (33). FAPP (now referred to as human pathological BSDL carrying the fucosylated J28 glycotope [pBSDL-J28]) was first characterized in human tumoral pancreas (34) and later on in human pancreatic tumor cell lines (35)(36)(37) using the murine J28 mAb (mAbJ28). mAbJ28 recognizes a carbohydrate-dependent antigenic structure (31), termed J28 glycotope, located within the O-glycosylated mucin-like C-terminal domain of pBSDL-J28 (38,39).…”
mentioning
confidence: 99%